Respuesta :

Answer:

Option A is correct.

Step-by-step explanation:

Given the equation: [tex]y = \frac{1}{2}x +3[/tex]     ......[1]

Fin the intercept of the equation:

x -intercept states that the line crosses the x-axis

Substitute y= 0 in [1] and solve for x

[tex]0= \frac{1}{2}x +3[/tex]

Multiply both sides by 2 we get;

[tex]0 = x+ 6[/tex]

Subtract 6 from both sides we get;

[tex]x = -6[/tex]

x-intercept: (-6, 0)

y-intercept states that the line crosses the y-axis.

Substitute the value of x = 0 and solve for y:

[tex]y = \frac{1}{2}(0)+3[/tex]

Simplify:

y = 3

y-intercept  = (0, 3)

Using these points (-6, 0) and (0, 3) plot the graph of the line as shown below.


Ver imagen OrethaWilkison

Answer:

Option D

Step-by-step explanation: